2022
DOI: 10.1002/adhm.202202221
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Conductive Hydrogel Scaffolds for Neural Cell Differentiation

Abstract: Multielectrode arrays would benefit from intimate engagement with neural cells, but typical arrays do not present a physical environment that mimics that of neural tissues. It is hypothesized that a porous, conductive hydrogel scaffold with appropriate mechanical and conductive properties could support neural cells in 3D, while tunable electrical and mechanical properties could modulate the growth and differentiation of the cellular networks. By incorporating carbon nanomaterials into an alginate hydrogel matr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 57 publications
0
21
0
Order By: Relevance
“…Furthermore, harvested materials such as Matrigel suffer from large batch-to-batch variability (69). More recently, synthetic materials, including polyethylene glycol (PEG), polyacrylamide, and peptide amphiphile hydrogels, as well as semi-synthetic materials like alginate, have been used because they are well-defined and highly tunable systems, enabling carefully defined interrogation into how specific matrix properties influence cell fate (16,21,(70)(71)(72)(73)(74)(75). Previous work using viscoelastic alginate hydrogels revealed that hNPCs exhibit greater transcriptional differences in response to changes in stress relaxation rate compared to changes in hydrogel stiffness and cell-adhesive ligand concentration; however, the range of stiffness profiled was significantly higher than the stiffness of our HELP hydrogels used in the present manuscript, and no nonstress-relaxing alginate was included as a potential control (16).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, harvested materials such as Matrigel suffer from large batch-to-batch variability (69). More recently, synthetic materials, including polyethylene glycol (PEG), polyacrylamide, and peptide amphiphile hydrogels, as well as semi-synthetic materials like alginate, have been used because they are well-defined and highly tunable systems, enabling carefully defined interrogation into how specific matrix properties influence cell fate (16,21,(70)(71)(72)(73)(74)(75). Previous work using viscoelastic alginate hydrogels revealed that hNPCs exhibit greater transcriptional differences in response to changes in stress relaxation rate compared to changes in hydrogel stiffness and cell-adhesive ligand concentration; however, the range of stiffness profiled was significantly higher than the stiffness of our HELP hydrogels used in the present manuscript, and no nonstress-relaxing alginate was included as a potential control (16).…”
Section: Discussionmentioning
confidence: 99%
“…wave, wrinkle, island-bridge, origami, textile, and crack), which allows for conformability, high electron/hole mobility, low impedance/resistance, high throughput, and satisfactory sensing performance. [24][25][26][27][28] For biomolecule detection, as biomolecules could not directly produce detectable signals, biosensors generally need an extra biotransducer to selectively recognize molecules and subsequently produce electrical or optical signals. Hence, it is necessary to summarize efficient biotransduction strategies for better soft biosensors.…”
Section: Yuanyuan Tianmentioning
confidence: 99%
“…In particular, it is viscoelasticity that is able to better mimic mechanical features of natural ECM, allowing larger neurite network construction. [ 119 ] Moreover, to induce the neuronal differentiation of BMSCs, Chen and colleagues fabricated AHA‐MA/Col hybrid hydrogel microfibers composed of collagens and aldehyde‐methacrylate dual‐ functionalized HA, which possessed orthogonal nano‐alignment and viscoelasticity owing to Schiff base formation of reversible imine crosslinks and microfluidic technique. They revealed the co‐effects of nano‐alignment and viscoelasticity on neurogenesis and demonstrated that such cooperation not only improved PC12 cells morphogenesis but also allowed neuronal differentiation of BMSCs, including up‐regulation of neurogenic genes expression, such as MAP‐2, nestin, NF‐L, NF‐M, and NSE, and neuronal specific protein Tuj‐1.…”
Section: Applications Of Energy‐dissipative Hydrogels In Tissue Regen...mentioning
confidence: 99%